Evaluating profitability of soil-renovation investments under crop rotation constraints in Finland - Purola, Tuomo; Lehtonen, Heikki (Elsevier BV, 2020)
Increasing the resource use efficiency of agricultural production is considered as a central element in Sustainable Intensification (SI) of agriculture, which is a promising strategy to satisfy increasing demand for food while reducing negative impacts on farm economy and environment. One challenge for SI is that degradation of agricultural soils and resulting crop yield losses are affecting negatively farmers' incomes and environment. This study analyses economic profitability of soil renovation investments aimed for tackling soil compaction in a regional context of south-west Finland, where some individual land parcels are compacted on many farms, implying crop yield losses, which we assume as −30%. We use a dynamic optimisation farm model with multiple input-use responses on crop yields. Explicit field parcel-specific crop-rotation constraints are accounted for in solving the farmers' decision problem of soil-renovation investments. Our results calculated over a 30 year time period suggest that soil-renovation investments are profitable since they produce a positive net present value (NPV) assuming 2000–2014 average crop prices, at all discount rates up to 10% when 30% yield decrease due to soil compaction is assumed. Higher than average crop prices would increase the value of soil renovation investment significantly while lower than average future crop prices would have a relatively small effect on the profitability of soil-renovation investment. The payback times of soil-renovation investments are approximately 8–11 years, depending on the discount rate, but largely independent on crop prices. Soil renovation increases production of higher valued crops, but the utilisation of the whole production potential of a farm is dependent on crop prices. We found that the full increased production potential may not be utilized after the renovation investment if not utilized already without the investment. It is concluded that one may recommend soil-renovation investments as a profitable long-term investment in a typical case, but one cannot recommend the soil renovation if no significant yield gains are possible, or if only low valued crop are to be produced. Nevertheless the field parcel-specific restrictions to avoid soil compaction after the renovation are important to be accounted for in evaluating the profitability of soil renovation at the farm level, since avoiding soil compaction is one part of more sustainable production strategy.
Keywords: soil compaction; Subsoiling; Dynamic optimisation; Crop rotation; Land use; Farm economics